Risk Analysis of Construction Work for the Construction of Gilmanuk - Mengwi Toll Road, Bali Province - AA Bagus Oka Khrisna Surya; Surya Aji Ermanto; Dinda One Mulyaningtyas; A.A Gde Sanjaya Putra (Jurnal Teknologi Transportasi dan Logistik, 2023)
Risk is the frequency of the emergence of an unfavorable condition and how much the consequences are caused and apply to all aspects of life, one of which is the construction project where the success of a construction project can be seen from how well the project is able to explore the risks that will occur, when viewed from the wide scope of the project, road construction projects have greater risks than building construction projects. The Gilimanuk – Mengwi toll road project is planned to be the second toll road to be built on the island of Bali which has a length of 96.21 km and passes through 3 regencies using a concession scheme with the aim of development to facilitate the flow of logistics transportation on the island of Bali.This study aims to determine the risk of building the Gilimanuk - Mengwi toll road and mitigate the risk that is included as a high risk criteria. The data collection method was carried out with literature studies and interviews using the questionnaire of the selected respondents, namely PUPR Bina Marga who will be directly involved in the implementation of the project. Process the risk level determination data using the probability x impact matrix with the Likert assessment scale. The results were obtained that there were 4 criteria and 12 sub-criteria of risk that were included as high risk with mitigation in general namely strengthening coordination between stakeholders in the preconstruction, always refer to the applicable rules and the application of technical implementation in the field practically and efficiently.